Doing deals in a global law firm: the reciprocity of institutions and work - Smets, M (2008)
Since the early 1990s, institutional approaches to organizations have increasingly focused on explaining the role of agency in processes of institutional creation and transformation. The paradox of embedded agency, the question of how actors can become motivated and enabled to transform supposedly taken-for-granted practices, structures and norms has become the fundamental puzzle of contemporary institutional theory. Recent attempts to resolve this puzzle under the label of “institutional work” focus on practices aimed at creating, maintaining, and disrupting institutions, but portray them as planned, discrete episodes that unfold in isolation from everyday organizational or social life. Thereby, the label highlights institutionalists’ current neglect of work in its literal meaning as actors’ everyday occupational tasks and activities. The detachment of institutional work from practical work constitutes a significant blind spot in institutionalists’ understanding of agency and calls for research that examines the reciprocity of institutions and work. Drawing on illuminating constructs from theories of practice, this study extends existing field-level approaches to the paradox of embedded agency. It argues for a practice-based institutionalism that focuses on individual actors and the role of their collective micro-level praxis in constituting macro-level institutions. It re-connects institutional arguments to every-day activity rather than organizational or managerial action, unpacks the micro-practices and micro–politics by which actors negotiate institutional contradictions and demonstrates the reciprocity of institutions and work. The research addresses the detachment of institutional and practical work through a single-case study of a global law firm’s banking group. It explores what banking lawyers do when they ‘do deals’ and how their practical work may attain institutional relevance. Positioned at the intersec-tion of local laws, international financial markets, commercial and professional logics, banking lawyers operate across multiple institutional frameworks. Observations and accounts of their work provide particularly rich insights into the dynamics of institutional persistence and change, because they illustrate empirically how contradictory institutionalized concepts, practices and logics are experienced, negotiated, and constituted at work.